A rare case of intrathoracic Gauzoma - Taishi Adachi; Hidenao Kayawake; Hiroshi Hamakawa; Yutaka Takahashi (Journal of Cardiothoracic Surgery)
Abstract Background Gauzoma is a foreign body reactive granuloma which is an extremely rare complication of thoracic surgery. We describe a case of a Gauzoma in which the gauzes were removed by mini-thoracotomy as a less invasive procedure, discovered incidentally after 35 years of follow-up. Case presentation A 51-year-old man was referred to our department for hyperhidrosis treatment, and imaging studies and biopsy confirmed the diagnosis of Gauzoma. As the Gauzoma gradually grew for a few years, surgical intervention was judged necessary, and the removal of the gauzes was performed in this case. A two-stage operation in two days was required to complete the surgery. The completion of gauze removal was confirmed in the second surgery using a postoperative computed tomography (CT) scan. The patient is currently doing well 17 months after surgery, and the size of granuloma unchanged. Conclusion We performed the removal of the gauzes as the treatment for Gauzoma. Although removing the gauze may have prevented its growth so far, careful follow-up is still needed.